Database of marine and freshwater algae resources of Andaman and Nicobar Islands - BALAKRISHNAN, M; SRIVASTAVA, R C; RAMACHANDRAN, M (The Indian Journal of Agricultural Sciences, 2012)
This repository can contribute and document all information of endemic algae resources of Andaman and Nicobar Islands and help prosperity. Database for algae resources of Andaman and Nicobar Islands has been developed with an aim of providing technical information to the researchers. About 313 freshwater algal species belonging to 15 families and 57 marine algal species belonging to 18 families have been included in this database among which 40 species are new records. It is needless to state that algal resources play an essential role in phytochemical industry, Pharmaceuticals, Sidha medicine, drug discovery research and agricultural economy in future. Algae products have a vital place in the list of essential commodities in the day-to- day life of common person. When compared to Indian mainland, very limited variety of algae is found in these islands. This database provides a common place for the entire information and user-friendly database. This database would be updated on a regular basis, so that it could provide status about the algae resources, which could be useful to scientists, research scholars, pharma companies and common person.